Left-right brain hemisphere dominance among first semester computer science students in introductory computer programming course - Othman, Mahfudzah (Universiti Teknologi MARA Pahang, 2009)
The study was carried out to investigate the left or right brain dominance among Computer Science students who enrolled in the Introductory Programming course offered in Universiti Teknologi MARA (UiTM). The investigation of their brain dominances is to further understand the students' thinking and learning preferences towards the course. A selected group of fifty-one first semester students from this university were asked to take the Cognitive Styles Analysis (CSA) in order to measure their brain dominances. The results show differences in brain lateralization among the respondents. The results can be used to improve students' learning processes and lecturers' abilities to deliver knowledge and skills that can meet their students' thinking preferences. This will improve the process of teaching and learning in the programming course.